2020
DOI: 10.3390/biom10111475
|View full text |Cite
|
Sign up to set email alerts
|

Dual Effects of Beta-Hydroxy-Beta-Methylbutyrate (HMB) on Amino Acid, Energy, and Protein Metabolism in the Liver and Muscles of Rats with Streptozotocin-Induced Type 1 Diabetes

Abstract: Beta-hydroxy-beta-methyl butyrate (HMB) is a unique product of leucine catabolism with positive effects on protein balance. We have examined the effects of HMB (200 mg/kg/day via osmotic pump for 7 days) on rats with diabetes induced by streptozotocin (STZ, 100 mg/kg intraperitoneally). STZ induced severe diabetes associated with muscle wasting, decreased ATP in the liver, and increased α-ketoglutarate in muscles. In plasma, liver, and muscles increased branched-chain amino acids (BCAAs; valine, isoleucine, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Hence, during diabetes, the flux through the CAC decreases [ 11 , 15 ]. It is very likely that these alterations have a fundamental role in impaired mitochondrial respiration and energy balance observed in the muscles, hearts, and kidneys of subjects with diabetes [ 4 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Basic Data On Glycolysis and The Cacmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, during diabetes, the flux through the CAC decreases [ 11 , 15 ]. It is very likely that these alterations have a fundamental role in impaired mitochondrial respiration and energy balance observed in the muscles, hearts, and kidneys of subjects with diabetes [ 4 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Basic Data On Glycolysis and The Cacmentioning
confidence: 99%
“…L-serine concentrations in plasma and tissues decrease in both T1DM [ 4 , 5 , 31 , 32 ] and T2DM [ 5 , 6 , 33 , 34 , 35 , 36 , 37 ]. The decrease in L-serine levels is probably due to two reasons.…”
Section: L-serine and Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proven repeatedly that in animal models of T1DM [ 32 , 33 , 34 ] and in patients with T1DM [ 35 , 36 ], the plasma BCAAs are significantly elevated compared to healthy controls. Untreated T1DM is characterized by hyperglycemia, increased food intake, increased fatty acid oxidation as an energy source, muscle wasting and muscle mitochondria dysfunction [ 37 , 38 ].…”
Section: Bcaas In Diseasesmentioning
confidence: 99%
“…It is suggested that the underlying mechanism involves disruptions in glycolysis and fatty acid oxidation. In T1DM, a decreased rate of glycolysis, reduced activity of citric acid enzymes and increased NADH/NAD + ratio due to enhanced fatty acid oxidation may contribute to the impaired BCAA catabolism as a consequence of the decreased supply of amino group acceptors (2-KG, PYR, oxaloacetate) and the inhibitory effect of NADH and acyl-CoAs on BCKD [ 32 , 39 ].…”
Section: Bcaas In Diseasesmentioning
confidence: 99%